Resiliensi nelayan terhadap ketersediaan sumberdaya perikanan di Kepulauan Karimunjawa - rani hafsaridewi; Achmad Fahrudin; Sulistiono Sulistiono; Dewayany Sutrisno; Sonny Koeshendrajana (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Resilience is a concept that cannot be generalized. This is because in analyzing resilience, the parameters that have been used for the resilience analysis is depend on the resilience context itself. It is important to establish which parameters are most important to be used for analyzing resilience of fishermen related to fisheries resources. Fishers' are the most vulnerable community and have a high depencency on natural resources. It is necessary to analyze of fishers' resiliences. The resilient fishing communities can increase their capacity to cope on socio-economic change. The purpose of this study is to determine the parameters that can be used to analyze resilience of the fishermen in small islands. The study was conducted from February to April 2018. The method used in this studyis expert judgment. Based on previous studies to analyze resilience used 6 dimensions, namely: social (21 parameters), economic (26 parameters), institutional (13 parameters), infrastructure (12 parameters), resources (9 parameters), and potential disaster (2 parameters), the total parameters are 83 parameters. Based on the result, 83 parameters were being indexing and only 53 parameters having values above 3,50 are used to analyze resilience assessment. The parameters that have the highest index in each dimension are the level of poverty (social dimension), number of livelihood (economic dimension), government role (institutional dimension), and fish catch (resource dimension).The selected parameters are used to analyze the fisher’s resilience in Karimunjawa islands.